Asuhan Keperawatan Post Partum Sectio Caesarea dengan Nyeri Akut melalui Penerapan Terapi Relaksasi Benson (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2026)
The postpartum period following Sectio Caesarea is often accompanied by acute pain due to surgical incisions, which may interfere with mobilization, breastfeeding, and maternal recovery. Effective pain management is essential to prevent further complications and enhance maternal comfort. In addition to pharmacological therapy, non-pharmacological interventions such as Benson relaxation therapy can be implemented. This study aimed to evaluate the application of Benson relaxation therapy in reducing acute pain among postpartum Sectio Caesarea mothers.This study employed a case study design involving four postpartum Sectio Caesarea patients (Ny. R, Ny. A, Ny. Y, and Ny. S) treated in the Ayyub Ward of RS Roemani Muhammadiyah Semarang in 2026. Data were collected through comprehensive nursing assessments, pain intensity measurement using a numeric rating scale, observation of mobilization ability, and evaluation before and after intervention.The results showed that after regular implementation of Benson relaxation therapy, all patients experienced a gradual decrease in pain intensity (from scale 4–7 to ≤3), improved comfort, better breathing control, and increased ability to perform early mobilization. Consistent nursing education, therapeutic guidance, and family involvement supported the effectiveness of the intervention. It can be concluded that Benson relaxation therapy is an effective, safe, and easily applicable nursing intervention for reducing acute pain in postpartum Sectio Caesarea patients.